Jules Bernard Luys on magnetic pathology. Issue 3 (September 2019) - Alvarado, Carlos S
In the mesmeric movement, one of the phenomena cited to defend the existence of magnetic and nervous forces was the visual perception of them in the form of luminous emanations from people, or effluvia. This Classic Text is an 1892 article by French neurologist, Jules Bernard Luys (1828–97), about the observation of such effluvia by hypnotized individuals. Interestingly, the luminous phenomena perceived from mentally diseased individuals and from healthy ones had particular properties. Luys's interest in this and other unorthodox phenomena were consistent with ideas of animal magnetism in the late neo-mesmeric movement, as well as with some physicalistic conceptions of hypnosis and the nervous system held at the time.